The feasibility of monetary integration within the SADC region - Nindi, Angelique Gugulethu (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2012)
The Southern African Development Community (SADC) aims to have a regional central bank by 2016 and a common currency by 2018. The member states are at the early stages of the process of regional economic integration, having launched a free trade area in 2008. Monetary integration is an advanced stage of regional economic integration that requires progressive changes in the participating countries. The purpose of this study is to determine the feasibility of monetary integration within the SADC countries and hence, provide policy recommendations to guide the integration process. To accomplish this, the study analyses the extent to which the member states meet the criteria for an optimum currency area (OCA) as well as the degree to which their economies are converging. The study finds that the main macroeconomic objectives of SADC countries differ due to a difference in the relative importance of monetary policy instruments in member states, which influences each country's commitment towards achieving the macroeconomic convergence targets and harmonising policies. A more appropriate approach to macroeconomic convergence would be to allow for variable speed, geometry and depth in each country as premature adherence to convergence targets could prevent a harmonisation of the economies in the future and possibly destabilise the union. In addition, the study investigates the importance and similarities of the monetary aggregate channel, the interest rate channel, the exchange rate channel and the credit channel in the transmission of monetary policy using VAR analysis. This is important when considering monetary integration because differences in transmission mechanisms can result in asymmetric behaviour between member states, which in turn will prevent harmonisation of their economies. The results of the analysis suggest that SADC member states display asymmetries in their responses to monetary policy shocks as well as the relative importance of transmission mechanisms. In addition, the results suggest that national monetary policy is generally inefficient in determining economic performance in the member states. Furthermore, the study finds that the failure to meet the OCA criteria implies that the SADC member states will respond asymmetrically to shocks within a monetary union. With no effective alternative adjustment mechanisms in place, the effects of the shocks will endure in union members and possibly widen existing cyclical variation. Hence, monetary integration would not result in harmonisation of the economies of member states. It is therefore, concluded that the SADC countries were not suitable for monetary integration at present.
Keywords: Southern African Development Community; Monetary policy -- Africa, Southern; Macroeconomics Africa, Southern -- Economic policy